Pengaruh kepemilikan asing terhadap penentuan Transfer pricing pada perusahaan farmasi - Meiriasari, Vhika; Nurkholis, Kgs. M. (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
The purpose of this study was to determine the effect of foreign ownership on transfer prices for pharmaceutical companies in the Indonesian stock market. When a foreign individual or entity owns the majority of a company, they are referred to as foreign shareholders. Instead, Transfer pricing refers to pricing practices that are mutually agreed upon between related parties. There is a special relationship between taxpayers when one taxpayer owns at least 25 percent of another taxpayer and exercises control over that taxpayer, or when two or more taxpayers have the same direct or indirect mandate. This study uses a quantitative approach. 7 sample companies were selected from 10 populations by purposive sampling technique and this study was based on secondary data. Using SPSS 26 and linear regression models for analysis. The results of the study state that foreign ownership has a positive effect on transfer prices